Jagung Betiring Pemberdayaan Masyarakat Berbasis Potensi Lokal Dengan Metode Participatory Action Research (PAR) - Sifwatir Rif’ah (LPPM IAI TABAH, 2022)
The Implementation of a society empowerment especially on Economic Sector and entrepreneurs through the processing of corn through the community service program (KKN) IAI TABAH 2019 is conducted at Betiring Village. This program aims to absorb labors, add community income through small and medium enterprises, improve creativity and local innovation that can be the typical products from Betiring-Sumber Agung, Brondong Lamongan and increase the selling value of corn commodities at Betiring, Sumber Agung Village, Brondong Sub-district, Lamongan District. Used qualitative research methods of Participatory Action Research (PAR). Data was collected through interviews, documentation, observation, and Focus Group Discussion. PAR data analysis is triangulation, seeking diversity and investigation with society.The solution that can be done is through the processing of the raw corn into the delicious, nutritious and preferredproduct as well as to be the typical local product that can compete with products from other areas. The results showed the implementation of community empowerment model: (1) Identify and analyze the problem, potential of human, natural and economic resources of communities to plan empowerment programs, (2) The Managed to foster a spirit and togetherness to improve knowledge and skills of entrepreneurship and cooperatives, (3) Execute a program extension, training (4) Monitoring and evaluation in the form of assistance